مفهوم القسم وأنواعه في القرآن الكريم - Salaeh, A. (Universiti Sains Islam Malaysia, 2024)
This research aims to study about the oath (al-Qasm) in the Quran and its types as introduced in the Quranic verses. In order to achieve the objective, the researcher emphasizes the meaning of (al-Qasm), its type, and the examples mentioned in the Holy Quran. Also, the decency of al-Qasm and the guidance to deal with a liar who swears by God had been mentioned. This research concludes about the punishment for those who commit false oath.